Nomina simplicium medicinarum ex synonymariis Medii Aevi collecta = Semantische Untersuchungen zum Fachwortschatz hoch- und spätmittelalter Drogenkunde - Daems, Willem Frans. (Studies in Ancient Medicine, 1993)
The lack of a well organised index of synonyms of plant names for the period of the later Middle Ages has increasingly been felt by historians, philologists and sociologists to be one of the big lacunas in their field. In his Boec van medicinen in Dietsche (Brill, 1967) Willem F. Daems presented in a Synonymarium van Middelnederlandse Plantennamen a summary of the plant names which occurred in a single text conceived in c. 1300. He now evaluates, assigns parameters for meaning to and in the majority of cases identifies the pharmaco-botanical material contained in about 100 medieval manuscripts and text editions (German, Dutch and English). The depth and breadth of the author's botanical knowledge is widely recognised and the combination of this with his background in history and philology make this book a long-awaited and indispensable standard reference work in the field.